The Sri Lankan spiny eel, Macrognathus pentophthalmos (Teleostei: Mastacembelidae), and its enigmatic decline - Pethiyagoda, Rohan; Silva, Anjana; Maduwage, Kalana; Kariyawasam, Lalith (Zootaxa, 2008)
The Sri Lankan population of the spiny eel previously assigned to Macrognathus aral Schneider (Teleostei: Mastacembelidae) is shown to be a distinct species, for which the name M. pentophthalmos Gronow is available. Macrognathus pentophthalmos is distinguished from its closest congener, M. aral, by having 14–16 dorsal spines and a pre-dorsal length of 43.3–46.8% of standard length (SL) (vs. dorsal spines 18–22 and pre-dorsal length 35.5–40.8% SL in M. aral). Macrognathus pentophthalmos differs from its only other Indian congener, M. guentheri Day, among other characters, by having 24 pairs of rostral tooth plates (vs. rostral tooth plates absent). With the present designation of a neotype, Rhynchobdella orientalis Bloch & Schneider (type locality East Indies to Sri Lanka) becomes an objective junior synonym of M. aculeatus Bloch. Although assessed as ‘common’ in 1980, the population of M. pentophthalmos suffered a precipitous decline in the following decade, the causes of which are unknown. The species may now be extinct.